2013
DOI: 10.1080/02755947.2012.754801
|View full text |Cite
|
Sign up to set email alerts
|

Biological Consequences of the Coaster Brook Trout Restoration Stocking Program in Lake Superior Tributaries within Pictured Rocks National Lakeshore

Abstract: The coaster Brook Trout Salvelinus fontinalis is a Lake Superior ecotype representing intraspecific variation that has been impacted by habitat loss and overfishing. Hatchery strains of Brook Trout derived from populations in Lake Superior were stocked into streams within Pictured Rocks National Lakeshore, Michigan, as part of an effort to rehabilitate adfluvial coaster Brook Trout. Wild and hatchery Brook Trout from three streams (Mosquito River, Hurricane River, and Sevenmile Creek) were examined for movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The Batchawana River was chosen as a natural control for the Magpie River, given that the two rivers have similar historical mean annual discharge, geology, chemical compositions and biological communities (Marty, Smokorowski, & Power, ; Smokorowski et al., ). Both resident (riverine) and potadromous (migratory between lentic and lotic environments) populations of Brook Trout have been documented in tributaries of Lake Superior (Leonard, Stott, Loope, Kusnierz, & Sreenivasan, ). Therefore, river segments where migrations from Lake Superior were prevented by a large waterfall at the downstream end were sampled to avoid the confounding factor of growth and condition differences likely to exist between resident and potadromous populations (Robillard, Casselman, McLaughlin, & Mackereth, ).…”
Section: Methodsmentioning
confidence: 99%
“…The Batchawana River was chosen as a natural control for the Magpie River, given that the two rivers have similar historical mean annual discharge, geology, chemical compositions and biological communities (Marty, Smokorowski, & Power, ; Smokorowski et al., ). Both resident (riverine) and potadromous (migratory between lentic and lotic environments) populations of Brook Trout have been documented in tributaries of Lake Superior (Leonard, Stott, Loope, Kusnierz, & Sreenivasan, ). Therefore, river segments where migrations from Lake Superior were prevented by a large waterfall at the downstream end were sampled to avoid the confounding factor of growth and condition differences likely to exist between resident and potadromous populations (Robillard, Casselman, McLaughlin, & Mackereth, ).…”
Section: Methodsmentioning
confidence: 99%
“…Hatchery supplementation has in the past been used as a means to augment or attempt to restore populations, and is likely to continue to be a component of restoration efforts in the future [11] , [13] . However, this practice often fails in creating self-sustaining populations or results in populations with reduced reproductive success, both with brook trout and with other salmonids [14] [16] . This is often ascribed to use of hatchery stocks that are not locally adapted to the habitats where they are introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent to the stocking, Stimmell (2006) observed that some of the wild brook trout exhibited migratory behavior as represented by juvenile outmigration. Although the stocking that took place may have led to limited introgression of Tobin Harbor genetics into the wild brook trout populations of these two streams, survival of these stocked fish was low and little or no successful spawning likely took place (Leonard et al, 2013). As a result, the movement and growth exhibited by the wild fish from these two streams is likely representative of the populations before the recent stocking took place.…”
Section: Methodsmentioning
confidence: 99%